The Application of Strict Liability and Vicarious Liability Principles in The Corporate Responsibility System in Corruption Criminal Cases in Indonesia - Pery Kurnia (Budapest International Research and Critics University, 2022)
Corruption has always been an interesting topic of conversation. The implementation of the Criminal Procedure Code in Indonesia, especially the Evidence stage in Court, in its implementation often occurs legal dynamics which is influenced by the evidence presented and the proof of the elements of the criminal act itself. The research method used in this study is a qualitative descriptive method. Based on the results and discussions that have been submitted, it can be concluded that a criminal act is considered committed by a corporation in Indonesia if it fulfills the provisions of Article 20 paragraph 2 of the Corruption Crime Act.